Retroffiting and Repairing Cooling Tower Structure Within A Tide Deadline - Benny Dwika Leonanda (METAL: Jurnal Sistem Mekanik dan Termal, 2023)
This project focused on the retrofitting of an aging cooling tower at PT. Sulfindo Adiusaha's Chlor Alkali Plant. The goal was to incorporate advanced technology and features into the cooling tower, in response to regulatory modifications and the need to upgrade older buildings to improve their resilience and performance. The existing wood structure of Cooling Tower T 9120 GH was replaced with a new FRP structure, and the Fill Pack was also replaced during the retrofit to restore the cooling capacity to the original design. The project was completed within a tight timeline of 10 days to ensure long-term reliability of operations at the plant.Following the commissioning of the new cooling tower structure, the retrofitted T 9120 GH cooling tower was able to deliver a cooling capacity of 10.8 million Kcal with an efficiency of 78.6%, indicating good condition and close to the original design performance. The maximum vibration data on the motor and base frame were recorded at 10 mm/s2, which is within the satisfactory category based on the CTI Standard. Motor bearing temperature was recorded at 65°C, indicating good performance.This project demonstrates the importance of timely upgrades to maintain plant operations and ensure long-term reliability. Retrofitting an aging cooling tower can improve its functionality, efficiency, and environmental impact. The success of this project also highlights that retrofitting can be done within a tight timeline, without compromising on safety or quality, provided proper planning and execution are in place.